Analisis Makna Leksikal pada Puisi “Mitos-Mitos Kecemasan” Karya Afrizal Malna - Dina Ayu Safitri; Haiva Nur Aziza (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to determine the lexical meaning of the poem “Myths of Anxiety” by Afrizal Malna. This type of qualitative descriptive research was used in this research, the data source in this research was the poem “Myths of Anxiety” by Afrizal Malna and similar journals. Researchers used data collection techniques by (1) reading the poem “Myths of Anxiety” by Afrizal Malna, (2) marking and writing the lexical meaning of each word in the poem “Myths of Anxiety” by Afrizal Malna. The researcher's steps in data analysis are (1) classifying or grouping words into tables, (2) analyzing the results of grouping words, (3) drawing conclusions based on the results of the analysis carried out. The results of this research show that the equivalent lexical meaning is longer than the connotative meaning and each stanza has a clear different in meaning according to the context of the words used.